2021
DOI: 10.1186/s12889-021-11547-5
|View full text |Cite
|
Sign up to set email alerts
|

Retention in HIV care and associated factors among youths aged 15–24 years in rural southwestern Uganda

Abstract: Background Retention in HIV care contributes to antiretroviral therapy adherence, which is a key factor for improved treatment outcomes and prevention of drug resistance. However, HIV treatment among the youths is characterized by loss to follow up, poor adherence to ART, risk of treatment failure and high mortality rates compared to young children and adults. There is limited information about factors associated with retention of youths in HIV care in rural settings in Uganda. We aimed to dete… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 42 publications
1
5
0
Order By: Relevance
“…The literature on retention shows mixed results concerning differences by sex. Similar to findings in our study showing higher retention among male ALHIV, a study from Uganda reported being male was independently associated with retention in HIV care [47]. Moreover, a study of prevalence and predictors of retention in care among adolescents in South Africa found male adolescents to be significantly more likely to be retained in care compared to females [48].…”
Section: Discussionsupporting
confidence: 89%
“…The literature on retention shows mixed results concerning differences by sex. Similar to findings in our study showing higher retention among male ALHIV, a study from Uganda reported being male was independently associated with retention in HIV care [47]. Moreover, a study of prevalence and predictors of retention in care among adolescents in South Africa found male adolescents to be significantly more likely to be retained in care compared to females [48].…”
Section: Discussionsupporting
confidence: 89%
“…The good retention rate is much better than reported in most previous studies. For example, Muwanguzi et al, reported 65% among the adolescents and young people aged 15-24 years [5], 29% by Izudi et al, [21], 69.5% by Cluver et al, [7] and by Zanooni et al, 89% [22] and 35.7%, Nimwesigwa et al, [11]. As for VLS, it was higher than reported by Hlophe et al, [4] at 55%, 65% by Simms et al, [9], 62% in Kenya [23] but lower than by Tugume et al, [6] at 81%.…”
Section: Discussionmentioning
confidence: 99%
“…Barriers to optimal VLS identi ed include; di culties nding transport money, unfriendly health settings, drug stock outs, prolonged waiting time, unfavorable school timetable, non-disclosure of HIV status and drug side effects [4][5][6][7][8][9][10]. Conversely, identi ed enablers include reliable stock-levels of drugs in the facilities, good attitude of health-workers, availability of transport money, social/family support, and positive peer in uence [4,7,8].…”
Section: Introductionmentioning
confidence: 99%
“…A more recent one by Muwanguzi et al. [7] reported a slightly better nding, with 65% of adolescents and young adults aged 15-24 years old in southwestern Uganda retained in care within one year. Indeed, routine programmatic data from Uganda showed that one-year retention among the children aged below 10 years was 87% while adolescents aged 10-19 were at 56%, far below the expected 95%.…”
Section: Introductionmentioning
confidence: 91%